Towards African Sovereignty in Social Progress - (:unkn) unknown (My University, 2025)
In a context marked by the decline of traditional Western aid and growing geopolitical uncertainty, African NGOs, their Northern counterparts, and other non-governmental actors engaged in social progress face profound shifts in their operating environment. This strategic note offers a clear analysis of these transformations and proposes concrete pathways to redefine the role, business model, and alliances of these actors within a framework of African sovereignty in social development.The diagnosis is unambiguous: public Western funding for social progress in Africa is shrinking under new political paradigms. This shift undermines the dominant model of African NGOs, historically dependent on external aid, and places Northern NGOs under increasing pressure to reinvent themselves.In this context, the note calls for a strategic transition based on five major pillars:1.Adapting Western NGOs to a technical partnership role, respecting local leadership and endogenous development logic.2.Empowering African NGOs through business model redesign, stronger civic anchorage, and enhanced strategic capacity.3.Mobilizing African financing through an underutilized triptych: philanthropic foundations, private enterprises, and African States.4.Building alliances of professional African NGOs, not based on size but on commitment, expertise, and transformative vision.5.Establishing a triangular pact of co-responsibility between professional NGOs, African economic operators, and governments, institutionalizing the co-construction of national social policies.The note also proposes a roadmap for the economic transition of African NGOs, focusing on optimizing remaining Western funding, coordinated advocacy for transitional support, defining economic sovereignty indicators, and recognizing Northern NGOs as providers of technical expertise.Far from advocating for a brutal rupture with previous models, this Pact embodies a tactical, deliberate, and ambitious transition grounded in
Keywords: African Research